26. DEVELOP THE MULTIPLEX-PCR METHOD FOR DIANOSING AND DISTINGUISHING HETERAKIS GALLINARUM BETWEEN HISTOMONAS MELEAGRIDIS (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to develop a multiplex-PCR method to simultaneously diagnose and differentiate the two species, Heterakis gallinarum and Histomonas meleagridis, coexisting in the intestines of chickens. Method: Intestinal and cecal tissue samples were processed to extract total DNA, and species-specific primer pairs were designed based on the 18S ribosomal gene sequences. Based on this, a multiplex-PCR method was developed and tested for the simultaneous diagnosis and detection of the two species, Heterakis gallinarum and Histomonas meleagridis.Results: Both primer pairs used in the reaction were designed to amplify the 18S ribosomal gene region. Specifically, the HGF-HGR primer pair generated a PCR product of 712 bp, which is specific to H. gallinarum, while the HMF-HMR primer pair produced a 331 bp PCR product, specific to H. meleagridis. The results of the multiplex-PCR method demonstrated the ability to simultaneously detect both H. gallinarum and H. meleagridis. Clinical samples with a total DNA concentration of 0.78 ng or higher yielded high-quality PCR results. Conclusion: The HMF-HMR primer pair was specifically designed for H. meleagridis, while the HGF-HGR primer pair was specific to H. gallinarum. Multiplex-PCR tests conducted on single templates, mixed templates, or DNA templates from other nematode species showed no non-specific primer binding reactions.
Keywords: Heterakis gallinarum; Histomonas meleagridis; multiplex-PCR; 18S rRNA